Why is the US Treasury contemplating becoming a lender of last resort for treasury securities? - Kenneth D. Garbade; John E. Kambhu (Federal Reserve Bank of New York, 2005)
The U.S. Treasury announced in August 2005 that it is exploring whether to provide a backstop securities lending facility for U.S. Treasury securities. This paper examines the conceptual basis for such a facility by comparing the market for borrowing and lending Treasury securities to the market for borrowing and lending money prior to the founding of the Federal Reserve System. An inelastic supply of currency in the nineteenth century led to periodic suspensions of convertibility of bank deposits; Congress authorized a system of Federal Reserve Banks to address the problem. A similarly inelastic supply of Treasury securities has contributed to several recent episodes of chronic settlement fails. A backstop lending facility would mitigate the fails problem by allowing the Treasury to act as a lender of last resort of Treasury securities during periods of unusual market stress.
Keywords: G18; H63; 330; Schatzpapier; Finanzmarkt; Pensionsgeschäft; Bankgeschichte; USA; Lender of Last Resort